A Comparison of Lipids and apoB in Asian Indians and Americans. Issue 1 (20th January 2021) - Singh, Kavita; Thanassoulis, George; Dufresne, Line; Nguyen, Albert; Gupta, Ruby; Narayan, K M Venkat; Tandon, Nikhil; Sniderman, Allan; Prabhakaran, Dorairaj
Background and aims: Apolipoprotein B (apoB) integrates and extends the information from the conventional measures of atherogenic cholesterol and triglyceride. To illustrate how apoB could simplify and improve the management of dyslipoproteinemia, we compared conventional lipid markers and apoB in a sample of Americans and Asian Indians. Methods: Data from the US National Health and Nutrition Examination Survey (NHANES) (11, 778 participants, 2009–2010, 2011–2012), and the Centre for Cardiometabolic Risk Reduction in South Asia (CARRS) cohort study in Delhi, India (4244 participants), 2011 were evaluated. We compared means and distributions of plasma lipids, and apo B using the Mann–Whitney U test and Fisher's exact test. A p value of < 0.05 was considered significant. Results: The plasma lipid profile differed between Asian Indians and Americans. Plasma triglycerides were greater, but HDL-C lower in Asian Indians than in Americans. By contrast, total cholesterol, non-HDL-C, and LDL-C were all significantly higher in Americans than Asian Indians. However, apoB was significantly higher in Asian Indians than Americans. The LDL-C/apoB ratio and the non-HDL-C/apoB ratio were both significantly lower in Asian Indians than Americans. Conclusion: Whether Americans or Asian Indians are at higher risk from apoB lipoproteins cannot be determined based on their lipid levels because the information from lipids cannot be integrated. ApoB, however, integrates and extends the information from triglycerides and cholesterol. Replacing the conventional lipid panel with apoB for routine follow ups could simultaneously simplify and improve clinical care.